Analisis Faktor yang Berhubungan dengan Length of Stay (LOS) Pasien Demam Berdarah Dengue (A91) di Rumah Sakit Citra Husada Jember - Putri Nur Hidayah; Efri Tri Ardianto (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2026)
Length of Stay (LOS) at Citra Husada Hospital frequently exceeds the established standard of seven days. Over the past two years, Dengue Hemorrhagic Fever (DHF) cases have increased by 71.1% and ranked among the top ten causes of inpatient admissions in 2024. Prolonged LOS may increase healthcare costs, whereas excessively short LOS may lead to readmission. This study aimed to identify factors associated with LOS among DHF patients. A quantitative cross-sectional design was employed involving 450 adult DHF patients, with 208 electronic medical records selected through simple random sampling. Data were analyzed using univariate and bivariate analyses with the chi-square test. The results showed that age (p < 0.001), comorbidity (p < 0.001), and nutritional status (p = 0.042) were significantly associated with LOS. In contrast, sex (p = 0.850), platelet count (p = 0.190), leukocyte count (p = 0.157), and hematocrit level (p = 0.090) were not significantly associated with LOS. Adult DHF patients with comorbidities and abnormal nutritional status were more likely to experience prolonged LOS. Hospitals should develop clinical pathways and provide targeted education to reduce the risk of prolonged hospitalization.